2009
DOI: 10.1099/jmm.0.005678-0
|View full text |Cite
|
Sign up to set email alerts
|

The subcutaneous inoculation of pH 6 antigen mutants of Yersinia pestis does not affect virulence and immune response in mice

Abstract: Two isogenic sets of Yersinia pestis strains were generated, composed of wild-type strains 231 and I-1996, their non-polar pH 6" mutants with deletions in the psaA gene that codes for its structural subunit or the whole operon, as well as strains with restored ability for temperature-and pH-dependent synthesis of adhesion pili or constitutive production of pH 6 antigen. The mutants were generated by site-directed mutagenesis of the psa operon and subsequent complementation in trans. It was shown that the loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
0
23
1
Order By: Relevance
“…pestis Psa fimbriae were previously found by us and others to bind to respiratory tract epithelial cells and interact with macrophages (31,37). Although the results of previous studies indirectly suggested that the Psa fimbriae are expressed in vivo (7,13,14,35,36), definitive evidence was lacking. In this study we have conclusively demonstrated by immunohistochemistry that the Psa antigen is produced in tissues of Y. pestis-infected mice.…”
Section: Discussioncontrasting
confidence: 44%
“…pestis Psa fimbriae were previously found by us and others to bind to respiratory tract epithelial cells and interact with macrophages (31,37). Although the results of previous studies indirectly suggested that the Psa fimbriae are expressed in vivo (7,13,14,35,36), definitive evidence was lacking. In this study we have conclusively demonstrated by immunohistochemistry that the Psa antigen is produced in tissues of Y. pestis-infected mice.…”
Section: Discussioncontrasting
confidence: 44%
“…Furthermore, such a pPCP 2 /Dlpp mutant strain exhibited drastically reduced tissue injury and a muted cytokine and chemokine induction in tissue homogenates and sera when compared with equivalent findings in WT, Dlpp and pPCP 2 mutant strains. We opted to cure the pPCP1 plasmid from WT and Dlpp Y. pestis strains rather than selectively delete the pla gene, as pesticin and pesticin-immunity protein do not contribute to the virulence of Y. pestis in the animal model (Anisimov et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The presence of the Y. pestis virulence plasmids was confirmed via PCR (Table 2). The Δ tatA mutant strain was next passaged through Swiss Webster mice by subcutaneous challenge, as routinely practiced by many labs [31], [33], [34], in order to ensure the genetic stability of the mutant strain after numerous in vitro growth steps needed to construct the mutant strain. The Y. pestis genome is unstable due to the presence of numerous IS 100 elements [35][37], and the passage of the mutant through an animal decreases the likelihood of a mixed population [2].…”
Section: Methodsmentioning
confidence: 99%